THE BALINESE GAMELAN PHENOMENON IN DIGITAL SIMULATION - Surya, I Gede Girinatha; Darma Putra, I Nyoman; Gelgel, Ni Made Ras Amanda (E-Journal of Cultural Studies; Vol 17 No 3 (2024): Volume 17 Number 3 August 2024, 2024)
Balinese gamelan as a product and heritage of Balinese culture has been faced with a new reality, that digital technology has taken some of the spirit behind the reality of Balinese gamelan. The phenomenon of digital gamelan is not something new. But for Balinese gamelan today, it is surprising. This problem shows that there are certain efforts in the development of Balinese art. This means that this problem is also generated by the influence of modern lifestyles, namely efficiency, which is expected to overcome other problems such as the difficulty of practicing time or gathering everyone to produce a gamelan music work. Therefore, the demands of those who expect gamelan music, for example, to accompany a dance, are considered to be able to shorten work time, while the use of digital technology can cut production costs. Thus, it is difficult to say whether digital gamelan produces a work of art in the same way as gamelan itself when played by several people. However, the meaning of Balinese gamelan has certainly shifted in the digital simulation phenomenon. Keywords : Phenomena, Balinese Gamelan, Simulation, Digitization